PENGARUH KOMITMEN KERJA GURU TERHADAP KINERJA MENGAJAR GURU SEKOLAH DASAR NEGERI SE-KECAMATAN GARUT KOTA - Annisa Fitria, - (2022)
This research is motivated by the less than optimal teaching performance of teachers. The purpose of this research is to gain an idea of how a teacher's work commitment to the performance of teaching a country's elementary school teachers. The method used is a descriptive method with a quantitative approach. The technique for collecting data in the study was that of using a questionnaire sent out directly to 84 research respondents. Weight means score (WMS) with the help of the SPSS 26.0 for Windows program, suggests that a teacher's work commitment falls in a very good category with a 4.33 average score and teacher teaching performance falls into an excellent category with a 4.67 average. Based on a coefficient correlation test between x and y variables, a value of 0.441 would fall under the category of a "moderate" relationship. The determination of the determinations obtained is that variable x affects 19.4 percent of the y, while the remaining 80.6% is affected by other factors. The significant results of the test amounted to 4,451 > 1,663 showing that ho was rejected and that ha was received, thus determining that coefficient correlation between x variables and y variables can be said to be significant. For regression analysis that shows 28,224 + 0.441x, it means that each addition of one variable point x makes the value on the y-variable increase by 0.441. Based on the results of research, it can be concluded that there is a positive and significant impact between a teacher's work commitment to teaching a country's primary school teacher a municipal district. Based on research results, the dimension of sustained commitment and the dimension assesses that learning has a lower score than other dimensions. If a teacher does not have a high ongoing commitment, then the teacher's lack of thought of reward and compensation is linked to wanting to leave school. That might suggest an optimum teaching performance at school as well. Hence, the headmaster needs to take care of the welfare of the teachers in the school whether it's material, permit or freedom, etc. And teachers are included in cia activities (sustainable development). Then, if teachers do not perform, analyzing and leverages the learning assessments optimally then the students' abilities in learning are unknown. Thus, teachers are unable to adopt models and strategies for future learning. Therefore, teachers should enhance their ability and be accompanied and include by the principal in training activities, seminars or workshops regarding assessments in learning. Then, the headmaster should always follow up with teachers regarding results of training so that teachers can be practiced in assessing learning. Keywords : teacher, teaching performance, work commitment